(untitled) (Journal of Nepalese Business Studies, 2021)
This research explores if possible fraudulent financial statement is present in private commercial banks in Nepal. This study examines the viability of Beneish M-score model in detecting probable earning manipulation considering the sample of 16 private commercial banks including the joint ventures. The published annual report (income statement and balance sheet) of the year 2018 and 2019 of respective banks are used as a secondary source of information. This research employs Beneish M-score equation and threshold value -2.22 as keys to analysis. The result shows even four banks are engaging in income manipulation, the Beneish model cannot identify the deception on the financial statement. Though the given model is suggested for manufacturing companies, the researcher has used it to explore the Banks—this is the limitation of this research. Further investigation of these tools combined with other fraud detection models is suggested to discover financial manipulation and relationship with the stock market return.